SCALE SCALE UP MOBILE VEGETABLE VENDORS IN PALANGKA RAYA CITY THROUGH FINANCIAL LITERACY AND DIGITAL MARKETING MENTORING - Syamsuri Syamsuri; Solikah Nurwati; Okta Malinda; Sri Mujiarti Ulfah (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service program aims to provide insight and knowledge about financial literacy, competitive pricing, sound financial management, how to hygienically and attractively package fish and vegetables, how to choose the right service and marketing strategies, and how to create technological innovations by following current trends such as delivery apps or social media. This Community Service activity, under the Community Empowerment Assistance Lecturer Service scheme, was conducted at the Berkah Bersama Mobile Vegetable Vendor Community in Palangka Raya City. The activities were implemented using various methods: Financial Literacy Socialization and Training, Training and Mentoring on the Use of Digital Marketing, Training on Appropriate Service and Marketing Strategy Management, and Training and Mentoring on skills in analyzing competitive pricing and how to manage and package products properly so that they appear fresh and attract buyers to increase profitability. The training delivery methods used were lectures, interactive dialogues, and hands-on demonstrations on the use of digital marketing applications. Keywords: Empowerment, Mobile Vegetable Vendors, Financial Literacy, Digital Marketing